EFEKTIVITAS MODEL PJBL DENGAN PENDEKATAN DEEP LEARNING TERHADAP PENGUATAN PROFIL PELAJAR PANCASILA PADA DIMENSI BERNALAR KRITIS, GOTONG ROYONG, DAN KREATIF DI SD BEREA TONDANO - Michella Christy Tania Supit; Dominikus Rojoki Manullang; Lidia Aprileny Hutahaean; Vinda Afnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the Project Based Learning (PjBL) model with a deep learning approach in strengthening the Pancasila Student Profile, particularly in the dimensions of critical thinking, collaboration (gotong royong), and creativity at SD Berea Tondano. This research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of two groups: an experimental class treated using PjBL with a deep learning approach and a control class taught using conventional methods. Data were collected through pretest and posttest instruments and analyzed using the N-Gain test to measure students’ learning improvement. The results showed that the mean N-Gain score of the experimental class (0.1667) was higher than that of the control class (0.1249), although both were categorized as low improvement. The normality test indicated that the data were normally distributed, fulfilling the assumptions for statistical analysis. In addition, the experimental class demonstrated a wider data distribution, indicating more varied individual improvements among students. In conclusion, the implementation of the PjBL model with a deep learning approach is more effective than conventional learning in strengthening the Pancasila Student Profile, particularly in the dimensions of critical thinking, collaboration, and creativity. This study implies that student-centered and innovative learning models can enhance the quality of learning in elementary education.